Ketahanan Kontraktual dalam Ekonomi Syariah: Perspektif Hukum dan Ekonomi - Khairi, Rifqil; Al Munawar, Muhammad Martadho Al Munawar; Nasrina, Nur; Santoso, Santoso (Journal of Legal Sustainability, 2024)
This study aims to analyze contractual resilience in Islamic economics from a legal and economic perspective, focusing on sharia principles that influence contract resilience in the face of modern economic dynamics. Contractual resilience in the sharia system is influenced by the principles of justice, transparency, and risk-sharing that provide better protection for the parties to the contract. In addition, this study also highlights the role of law and regulation in ensuring that sharia contracts remain in accordance with sharia principles and are able to face global economic challenges. The methods used in this study are literature studies and interviews with experts in economics and sharia law. Literature studies were conducted by analyzing books, journals, and regulations related to Islamic economics, while interviews were conducted to obtain in-depth views from practitioners and experts in the field of Islamic economics. The results of the study indicate that sharia contracts have higher resilience compared to conventional contracts, especially in the face of economic crises, due to the principles of risk-sharing and transparency in sharia contracts. However, this study also found challenges in the implementation of sharia contracts that are inconsistent in several institutions, as well as the need for innovation in sharia financial products that are more adaptive to global economic changes. In conclusion, although the resilience of sharia contracts is better, there is still a need to strengthen education, innovation, and regulation to ensure more effective implementation.